2006
DOI: 10.1063/1.2372702
|View full text |Cite
|
Sign up to set email alerts
|

Complementary organic field effect transistors by ultraviolet dielectric interface modification

Abstract: The realization of p- and n-type pentacene organic field effect transistors and an organic inverter stage is reported based on selective ultraviolet (UV) modification of the polymer dielectric in air. Apart from the UV radiation treatment, the device structures are identical. The achieved field effect carrier mobilities for both transistor types are ≈0.1cm2∕Vs. Similar performance data for both transistor types as well as an observed low current hysteresis qualify the UV treatment for organic complementary met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 9 publications
2
33
0
1
Order By: Relevance
“…The results are consistent with other reports, and a plausible explanation is that UV treatment creates excess negatively charged sites on the pentacene/PMMA interface. 6,7 Accordingly, the S.S. was enlarged and the V th positively shifted. However, the linear field-effect mobility ͑ FET ͒ was not affected by UV treatment and was about 0.1 cm 2 /V s for both devices.…”
Section: Resultsmentioning
confidence: 99%
“…The results are consistent with other reports, and a plausible explanation is that UV treatment creates excess negatively charged sites on the pentacene/PMMA interface. 6,7 Accordingly, the S.S. was enlarged and the V th positively shifted. However, the linear field-effect mobility ͑ FET ͒ was not affected by UV treatment and was about 0.1 cm 2 /V s for both devices.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have shown that the spatial and selective tuning of the ambipolar charge transport properties provides an effective way to improve the performance of complementarylike logic circuits based on ambipolar materials. 11,12 In this letter, we demonstrate conversion of the majority carrier type by thermal annealing in ambipolar OFETs based on the solution-processible quinoidal oligothiophene ͓QQT͑CN͒4͔. The fabrication of flexible organic inverters with improved performance suggests a reliable and unique approach for patterning by thermal lithography CMOS organic logic circuits with specified p-and n-region profiles in solution-processed thin films made from a monolithic organic semiconductor.…”
mentioning
confidence: 99%
“…Owing to this dual nature ambipolar materials open a route for the fabrication of complementary integrated circuits based on a single organic semiconductor in that one type of charge carrier transport can be selectively suppressed, for example via interface modification. [14,15] By adequately prepatterning the semiconductor/insulator interface, n-and p-type organic transistors can be produced next to each other on a common substrate and CMOS-like logic gates can thus be realized using a single organic semiconductor material. This might offer substantial processing advantages over CMOS-type logics relying on two organic semiconductors, one of p-type and the second of n-type.…”
mentioning
confidence: 99%